FOOD ESPUMAS AS A SIGNIFICANT COMPONENT OF MOLECULAR GASTRONOMY - Абрамова, Асьят (SWorldJournal, 2025)
This article examines the possibility of using food foams (foams) and the process of foaming (foaming) as one of the effective tools of molecular gastronomy. Molecular cuisine is one of the modern directions of gastronomy, which allows you to serve guest